Narrative of the voyage of H.M.S. Herald during the years 1845-51, under the control of Captain Henry Kellett, R.N, C.B.; being a circumnavigation of the globe; and three cruizes to the Arctic regions in search of Sir John Franklin. In two volumes ... - Seemann, Berthold, 1825-1871 (London : Reeve and Co., 2016)
"Seemann was the naturalist of the expedition. Chapter 8 gives a detailed description of the Fort Victoria district and its inhabitants in 1846."-- Strathern, G. M., & Edwards, M. H. (1970). Navigations, traffiques & discoveries, 1774-1848: A guide to publications relating to the area now British Columbia. Victoria, BC: University of Victoria, p. 265. ...